Using the synthetic form RS5 to obtain new introgressive lines of common wheat - R. O. Davoyan; I. V. Bebyakina; E. R. Davoyan; Y. S. Zubanova; D. M. Boldakov; D. S. Mikov; V. A. Bibishev; A. N. Zinchenko; E. D. Badaeva (Вавиловский журнал генетики и селекции)
The use of the gene pool of wild relatives, which have a significant reserve of genetic diversity, is of immediate interest for breeding common wheat. The creation and use of synthetic forms as “bridges” is an effective method of transferring valuable genetic material from wild relatives to cultivated wheat. For this purpose, genome addition, genome substitution and recombinant “secondary” synthetic forms have been created in the P.P. Lukyanenko National Center of Grain. The synthetic recombination form RS5 (BBAASDt ), in which the third genome consists of chromosomes of Aegilops speltoides (S) and Aegilops tauschii (Dt ), was obtained from crossing the synthetic forms Avrodes (BBAASS) and M.it./Ae. tauschii (BBAADt Dt ), in which the D genome from Ae. tauschii was added to the BBAA genomes of the durum wheat cultivar Mutico italicum. Introgression lines resistant to leaf rust, yellow rust and powdery mildew have been obtained from backcrosses with the susceptible common wheat cultivars Krasnodarskaya 99, Rostislav and Zhirovka. Twelve resistant lines that additionally have high technological characteristics of grain and flour have been selected. The cytological study (С-banding) has revealed chromosomal modifications in 6 of 8 lines under study. The rearrangements mainly affected the chromosomes of the D genome, 1D, 3D, 4D, 6D and 7D. It was found that in most cases the genetic material from the synthetic form RS5 in the studied lines was represented by substituted chromosomes from Ae. tauschii. In line 5791p17, the substitution of chromosomes 6D from Ae. tauschii and 7D from Ae. speltoides was revealed. Substitutions 4D(4Dt ), 6D(6Dt ) from Ae. tauschii and 7D(7S) from Ae. speltoides were obtained for the first time. Molecular analysis of 12 lines did not reveal effective leaf rust resistance genes, presumably present in synthetic forms of M.it./Ae. tauschii and Avrodes. It is assumed that the lines may carry previously unidentified genes for fungal disease resistance, in particular for resistance to leaf rust, from Ae. tauschii and Ae. speltoides.